2017
DOI: 10.1016/j.juro.2016.09.109
|View full text |Cite
|
Sign up to set email alerts
|

Parental Preference Assessment for Vesicoureteral Reflux Management in Children

Abstract: Introduction & objective Parents of children with vesicoureteral reflux are presented with a variety of management options that in many cases offer a similar risk-benefit ratio. In order to facilitate shared decision-making, parental preferences regarding VUR treatment options need to be acknowledged. This study aims to characterize the clinical experience of parents and elicit core themes affecting decision-making in regards to managing their child’s vesicoureteral reflux. Methods A semi-structured, qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(22 reference statements)
2
6
0
2
Order By: Relevance
“…Of the 13 primary parental preference themes identified in parent interviews by Tran et al, the most commonly considered treatment themes were efficacy, future UTI prevention, daily care burden, antibiotic resistance, and invasiveness. 5 Similar to our findings that cosmesis and cost are relatively less important attributes, only 19% of parents interviewed mentioned posttreatment cosmesis; treatment cost did not emerge as a primary theme. 5 Parental preference for success rate over cosmesis has been previously documented in pediatric urology.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Of the 13 primary parental preference themes identified in parent interviews by Tran et al, the most commonly considered treatment themes were efficacy, future UTI prevention, daily care burden, antibiotic resistance, and invasiveness. 5 Similar to our findings that cosmesis and cost are relatively less important attributes, only 19% of parents interviewed mentioned posttreatment cosmesis; treatment cost did not emerge as a primary theme. 5 Parental preference for success rate over cosmesis has been previously documented in pediatric urology.…”
Section: Discussionsupporting
confidence: 83%
“…Attributes were chosen based on clinical experience and prior qualitative and quantitative studies. [5][6][7][8] In each question, respondents were asked to select the most and least important attribute in choosing a VUR treatment for their child. The attributes included in each BWS question were prepared according to an experimental design using Sawtooth MaxDiff.…”
Section: Object Case Bwsmentioning
confidence: 99%
“…In studies of parents' preferences, Tran et al identified 13 themes that influenced the parents' choice of VUR treatment. The four most common were the prevention of future UTI, the efficacy rate of treatment, the burden of daily maintenance and the risk of antibiotic resistance [137]. Capozza et al evaluated parental treatment preferences in children with VUR grade III who had been on CAP for at least six months.…”
Section: What Do Parents Think?mentioning
confidence: 99%
“…Konstruktiv kann nur gut gegen eine Methode votiert werden, wenn eine adäquate Alternative anzubieten ist. Eltern präferieren generell operative Methoden, die das HWI-Risiko minimieren, ein gutes Outcome haben und mit der aktuellen familiären Situation vereinbar sind [3]. Letzteres scheint in der heutigen Zeit nahezu gleichbedeutend mit einem möglichst geringen zeitlichen Aufwand zu sein.…”
Section: Introductionunclassified
“…Letzteres scheint in der heutigen Zeit nahezu gleichbedeutend mit einem möglichst geringen zeitlichen Aufwand zu sein. Für etwa 60 % der Eltern war der Grad der mit der entsprechenden Reflux-Behandlung einhergehenden Invasivität für eine Therapieentscheidung ausschlaggebend [3]. Leider gibt es weder in der zitierten Studie noch generell ein allgemein akzeptiertes adäquates Maß für "Invasivität" im Kindesalter [3].…”
Section: Introductionunclassified